Preparation process of ultra-clean container with hydrofluoric acid-resistant lining film
By corona treatment of the PFA lining film, and adhesives prepared with modified bentonite and nanosilica and other materials, combined with silane coupling agent to treat the HDPE surface, the problem of degradation of HDPE material in a strong acid environment is solved, and the firm combination of the PFA lining film and HDPE material and excellent acid resistance are achieved.
Patent Information
- Application Number
- CN202411912143.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-18
AI Technical Summary
HDPE materials have deteriorated performance when facing strong acids such as high concentrations of sulfuric acid and hydrofluoric acid, and the adhesion between the PFA lining film and the HDPE material is insufficient, making it difficult to form a firm bond.
By corona treatment on the PFA lining film, its surface energy and adhesion are improved, and adhesives prepared by modified bentonite and nanosilica are used to treat the HDPE surface with silane coupling agent to achieve a firm bond between the PFA lining film and the HDPE material.
It significantly improves the resistance to hydrofluoric acid and high concentration sulfuric acid of HDPE materials, ensures the firm combination of the PFA lining film and HDPE materials, and enhances the overall performance of the ultra-clean container.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer materials and relates to a preparation process of an ultra-clean container with a hydrofluoric acid-resistant lining film. Background Art
[0002] High-density polyethylene (HDPE) has excellent corrosion resistance due to its stable molecular structure. This structure makes it not easily corroded by a variety of chemicals and shows good corrosion resistance in common weak acid environments. Although HDPE performs well in weak acid environments, it will affect the performance of HDPE materials when facing strong acids, such as high-concentration concentrated sulfuric acid and concentrated nitric acid. At the same time, HDPE materials have poor corrosion resistance to hydrofluoric acid, while fusible polytetrafluoroethylene (PFA) has similar chemical resistance to polytetrafluoroethylene and can resist corrosion from almost all known strong acids, strong bases, organic solvents and oxidants.
[0003] Therefore, in order to improve the resistance of ultra-clean containers made of HDPE to hydrofluoric acid and high-concentration concentrated sulfuric acid, a layer of PFA lining film is added to the inner wall of the HDPE barrel. However, the melting points of PFA and HDPE materials are quite different, and the surface energies of HDPE and PFA are both low. The wettability of the adhesive on their surfaces is poor, and it is difficult to form a uniform wetting layer, which reduces the contact area between the adhesive and the material surface, thereby reducing the adhesion.
[0004] Therefore, it is necessary to develop a new process that can firmly combine the PFA liner film with the HDPE material, so as to improve the resistance of HDPE plastic products to hydrofluoric acid and high-concentration concentrated sulfuric acid. Summary of the invention
[0005] The object of the present invention is to provide a preparation process of an ultra-clean container with a hydrofluoric acid resistant lining membrane. Through the process of the present invention, the ultra-clean container of the PFA lining membrane and the HDFE material can be combined together to obtain an ultra-clean container with excellent resistance to hydrofluoric acid and 98% concentrated sulfuric acid.
[0006] The purpose of the present invention can be achieved by the following technical solutions: A preparation process of an ultra-clean container with a hydrofluoric acid-resistant lining film, wherein the ultra-clean container substrate and the lining film are bonded by an adhesive, wherein the container substrate is made of high-density polyethylene, and the lining film is made of fusible polytetrafluoroethylene, comprising the following preparation processes: S1. Melting fusible polytetrafluoroethylene at 320-335°C, then extruding, maintaining the temperature and expanding the fusible polytetrafluoroethylene to a size that matches the mold through a blowing process, to obtain an inner lining film having a thickness of 0.3 mm, wherein the extrusion speed is 18-22 m / min, the extrusion pressure is 8-12 MPa, and the blowing pressure is 0.5-0.7 MPa; S2, treating the inner lining film by a corona process, wherein the parameters of the corona treatment process are: voltage of 10-13 kV, discharge frequency of 20-23 KHz, to prepare a pretreated inner lining film; S3. Coat the inner wall of the ultra-clean container substrate with a silane coupling agent KH560 solution with a mass fraction of 15%. After sufficient drying, evenly apply the adhesive on the pretreated lining film surface, and then bond it to the inner wall of the ultra-clean container with the adhesive. Maintain the pressure by blowing, and the blowing pressure is 0.5~0.7MPa. After curing, it is subjected to a press coating treatment for 1~2h. After washing with deionized water and drying at room temperature, the ultra-clean container with a hydrofluoric acid-resistant lining film is obtained, wherein the pressing temperature is 20~40°C and the pressure is 0.1~0.2MPa.
[0007] As a preferred technical solution of the present invention, in step S3, the curing temperature is 35-45°C and the curing time is 5-8h.
[0008] As a preferred technical solution of the present invention, in step S3, the preparation process of the adhesive is as follows: Step 1: Place 80-100 parts of silicone resin and 20-25 parts of epoxy resin in a reaction kettle, heat and stir at 130-155° C. for 3-5 hours to obtain a mixture A; Step 2: Add 4-7 parts of modified bentonite to mixture A, stir at 60-75° C. for 30 min, and continue to add 3-5 parts of nano-silicon dioxide and continue to stir for 30 min to obtain mixture B; Step 3: Continue to add 25-35 parts of curing agent, 1-3 parts of accelerator, 5-7 parts of diluent and 1-3 parts of silane coupling agent, and stir at room temperature for 8-10 minutes to obtain the adhesive.
[0009] As a preferred technical solution of the present invention, in step 1, the organic silicone resin is methyl silicone resin.
[0010] As a preferred technical solution of the present invention, in step 2, the preparation process of the modified bentonite is as follows: At room temperature, aluminum chloride and deionized water are mixed in a mass ratio of 1:5, stirred at a speed of 200 r / min for 2-3 hours, bentonite is added and stirred for 1-3 hours, and the pretreated bentonite is obtained after filtration; bentonite and polyoxyethylene hydrogenated castor oil are mixed in a mass ratio of 1: (0.5-0.8), stirred at a speed of 300 r / min for 30 minutes, and then allowed to stand for 25-35 minutes, washed with deionized water, dried at 95-105° C. for 7-9 hours, and then ground by a ball mill at a speed of 400 r / min for 2 hours and passed through a 200-mesh sieve to obtain the modified bentonite.
[0011] As a preferred technical solution of the present invention, in step three, the diluent is ethylene glycol diglycidyl ether.
[0012] As a preferred technical solution of the present invention, in step three, the curing agent is one of ethylenediamine, diethylenetriamine and polyamide curing agent.
[0013] As a preferred technical solution of the present invention, in step three, the accelerator is one of accelerator DMP-30 and 2-ethyl-4-methylimidazole.
[0014] As a preferred technical solution of the present invention, in step three, the silane coupling agent is one of KH550, KH560 and KH570.
[0015] As a preferred technical solution of the present invention, the stirring speed during the preparation process of the adhesive is 200-270 r / min.
[0016] The present invention obtains a PFA liner film by blow molding, and performs surface treatment on the PFA liner film by corona treatment, and the corona treatment can increase the energy of the material surface, thereby improving its adhesion. The corona treatment uses high frequency and high voltage to perform corona discharge on the surface of the PFA liner film, generates low-temperature plasma, and generates polar groups on the PFA surface, thereby increasing the surface energy of the PFA liner film. The increase in surface energy helps to improve the wettability and adhesion between the PFA liner film and the adhesive. In addition, while the plasma generated during the corona treatment bombards the PFA surface, the roughness of the PFA surface is increased. This rough surface structure increases the contact area and mechanical bite force between the PFA and the adhesive, which helps to improve the adhesion strength. Therefore, the adhesion between the PFA liner film treated with the corona and the adhesive is greatly enhanced.
[0017] The main material of the adhesive used in the present invention is composed of silicone resin, and epoxy resin is added to improve the adhesion of the adhesive to the adherend, thereby enhancing the overall connection strength.
[0018] Bentonite particles are small and can fill the tiny pores and cracks in the adhesive to form a dense structure. This dense structure can block the intrusion of water and other penetrating substances, thereby improving the adhesive's impermeability. Bentonite also has the property of swelling when it comes into contact with water. When water tries to penetrate into the adhesive, the bentonite particles absorb the water and swell. This swelling action further blocks the pores and cracks, strengthens the waterproof barrier of the adhesive, and improves the adhesive's impermeability.
[0019] In the present invention, the polyhydroxy cations produced by the hydrolysis of aluminum chloride are first mixed with bentonite, and the cation exchange of bentonite is utilized to make the polyhydroxy cations enter the interlayer of bentonite, thereby opening the interlayer domain and increasing the interlayer distance. Polyoxyethylene hydrogenated castor oil is then added, and when polyoxyethylene hydrogenated castor oil and bentonite are subjected to modification reaction, the surfactant molecules are adsorbed on the surface of the bentonite particles, and interact with the functional groups such as hydroxyl groups on the surface of the bentonite through their hydrophilic groups, and this adsorption changes the charge state and polarity of the surface of the bentonite particles, and also increases the hydrophilicity of the particle surface. At the same time, the hydrophobic groups of the surfactant molecules are oriented to the outside, forming a layer of hydrophobic barrier. This structural change makes the modified bentonite have better wettability, dispersibility and stability in water, thereby improving the contact area and interaction force with other materials in the adhesive and with the PFA material.
[0020] When preparing the adhesive, firstly, the modified bentonite is mixed with the silicone resin to enhance the adhesive's adhesion, and then nano-silicon dioxide is added. Since bentonite has good adhesion and meshing properties, and nano-silicon dioxide, due to its ultra-fine characteristics, can more effectively reinforce and increase the viscosity of the colloid, thereby improving the adhesive strength. The addition of nano-silicon dioxide can fill the pores inside the bentonite and the adhesive matrix material, thereby increasing the density and stability of the adhesive.
[0021] Coating a layer of silane coupling agent on the surface of HDPE material can introduce polar groups on its surface to improve its compatibility with the adhesive and bonding strength.
[0022] Beneficial effects of the present invention: The present invention improves the adhesion of the adhesive to the surface of the PFA material by corona treatment, and obtains the ultra-clean container with an inner lining film by bonding with the inner wall of the HDPE ultra-clean container whose surface is treated with a silane coupling agent. In the environment of hydrofluoric acid and high-concentration concentrated sulfuric acid, a layer of fluoride compound protective film is formed on the surface of the PFA material, and the protective film can effectively prevent erosion and penetration, thereby achieving excellent resistance to hydrofluoric acid and high-concentration concentrated sulfuric acid. DETAILED DESCRIPTION
[0023] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0024] In the following examples and comparative examples: The container used in the present invention is a barrel cover and a barrel body connected in a spiral manner, the barrel cover can be opened, and the mold used in preparing the liner film is consistent with the shape of the container; PFA: purchased from Daikin Fluorochemical (China) Co., Ltd., brand name AP-231SH; The organosilicon resin was methyl silicone resin purchased from Hubei Hengjingrui Chemical Co., Ltd.; Aluminum chloride: purchased from Shandong Yukang Chemical Co., Ltd.; Bentonite: purchased from Hubei Kewode Chemical Co., Ltd.; Polyoxyethylene hydrogenated castor oil: purchased from Wuhan Xindadi Environmental Protection Materials Co., Ltd. Nano-silicon dioxide: purchased from Hubei Fangde New Materials Co., Ltd.; 2-Ethyl-4-methylimidazole: purchased from Shanghai Kaisai Chemical Co., Ltd., product number: 931-36-2; Ethylene glycol diglycidyl ether: purchased from Hubei Wonder Chemical Co., Ltd.; KH550 and KH560 were purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0025] Example 1 Preparation of modified bentonite: At room temperature, aluminum chloride and deionized water are mixed in a mass ratio of 1:5, stirred at a speed of 200 r / min for 2 hours, bentonite is added and stirred for 1-3 hours, and pretreated bentonite is obtained after filtration; bentonite and polyoxyethylene hydrogenated castor oil are mixed in a mass ratio of 1:0.5, stirred at a speed of 300 r / min for 30 minutes, and then allowed to stand for 25 minutes, washed with deionized water, dried at 95°C for 7 hours, and then ground by a ball mill at a speed of 400 r / min for 2 hours and passed through a 200-mesh sieve to obtain the modified bentonite.
[0026] Preparation of adhesive: Step 1: 80 parts of silicone resin and 20 parts of epoxy resin were placed in a reaction kettle by weight, and stirred at 130° C. and 200 r / min for 3 hours to obtain a mixture A; Step 2: Add 4 parts of modified bentonite to mixture A, stir at 200 r / min for 30 min at 60° C., then add 3 parts of nano-silicon dioxide and continue stirring for 30 min to obtain mixture B; Step 3: Continue to add 25 parts of diethylenetriamine, 1 part of 2-ethyl-4-methylimidazole, 5 parts of ethylene glycol diglycidyl ether and 1 part of KH550, and stir at room temperature at a speed of 200 r / min for 8 minutes to obtain the adhesive.
[0027] Preparation of ultra-clean containers with hydrofluoric acid-resistant lining membranes: S1. Melting fusible polytetrafluoroethylene at 320°C, extruding, maintaining the temperature and expanding the fusible polytetrafluoroethylene to a size that is consistent with the mold through a blowing process, to obtain an inner lining film having a thickness of 0.3 mm, wherein the extrusion speed is 18 m / min, the extrusion pressure is 8 MPa, and the blowing pressure is 0.5 MPa; S2, treating the inner lining film by a corona process, wherein the parameters of the corona treatment process are: voltage of 10 kV, discharge frequency of 20 KHz, and treatment time of 10 s, to prepare a pretreated inner lining film; S3. Coat the inner wall of the ultra-clean container substrate with a silane coupling agent KH560 solution with a mass fraction of 15%. After sufficient drying, evenly apply the adhesive on the pretreated surface of the lining film, and then bond it to the inner wall of the ultra-clean container with the adhesive. Maintain the pressure by blowing, and the blowing pressure is 0.5 MPa. After curing at 35°C for 5 hours, it is pressed for 1 hour. After washing with deionized water and drying at room temperature, the ultra-clean container with a hydrofluoric acid-resistant lining film is obtained, wherein the pressing temperature is 20°C and the pressure is 0.1 MPa.
[0028] Example 2 Preparation of modified bentonite: At room temperature, aluminum chloride and deionized water are mixed in a mass ratio of 1:5, stirred at a speed of 200 r / min for 2.5 hours, bentonite is added and stirred for 2 hours, and the pretreated bentonite is obtained after filtration; bentonite and polyoxyethylene hydrogenated castor oil are mixed in a mass ratio of 1:0.6, stirred at a speed of 300 r / min for 30 minutes, and then allowed to stand for 30 minutes, washed with deionized water, dried at 100°C for 8 hours, and then ground by a ball mill at a speed of 400 r / min for 2 hours and passed through a 200-mesh sieve to obtain the modified bentonite.
[0029] Preparation of adhesive: Step 1: 90 parts of silicone resin and 22 parts of epoxy resin were placed in a reaction kettle by weight, and stirred at 145° C. and 240 r / min for 4 hours to obtain a mixture A; Step 2: Add 5 parts of modified bentonite to mixture A, stir at 65° C. and 230 r / min for 30 min, then add 4 parts of nano-silicon dioxide and continue stirring for 30 min to obtain mixture B; Step 3: Continue to add 30 parts of diethylenetriamine, 2 parts of 2-ethyl-4-methylimidazole, 6 parts of ethylene glycol diglycidyl ether and 2 parts of KH550, and stir at room temperature at a speed of 240 r / min for 9 minutes to obtain the adhesive.
[0030] Preparation of ultra-clean containers with hydrofluoric acid-resistant lining membranes: S1. Melting fusible polytetrafluoroethylene at 328°C, extruding, maintaining the temperature and expanding the fusible polytetrafluoroethylene to a size that is consistent with the mold through a blowing process, to obtain an inner lining film having a thickness of 0.3 mm, wherein the extrusion speed is 20 m / min, the extrusion pressure is 10 MPa, and the blowing pressure is 0.6 MPa; S2, treating the inner lining film by a corona process, wherein the parameters of the corona treatment process are: voltage of 11 kV, discharge frequency of 21 KHz, and treatment time of 9 s, to prepare a pretreated inner lining film; S3. Coat the inner wall of the ultra-clean container substrate with a silane coupling agent KH560 solution with a mass fraction of 15%. After sufficient drying, evenly apply the adhesive on the pretreated surface of the lining film, and then bond it to the inner wall of the ultra-clean container with the adhesive. Maintain the pressure by blowing, and the blowing pressure is 0.6MPa. After curing at 40°C for 6h, it is pressed for 1.5h. After washing with deionized water and drying at room temperature, the ultra-clean container with a hydrofluoric acid-resistant lining film is obtained, wherein the pressing temperature is 30°C and the pressure is 0.15MPa.
[0031] Example 3 Preparation of modified bentonite: At room temperature, aluminum chloride and deionized water are mixed in a mass ratio of 1:5, stirred at a speed of 200 r / min for 3 hours, bentonite is added and stirred for 3 hours, and the pretreated bentonite is obtained after filtration; bentonite and polyoxyethylene hydrogenated castor oil are mixed in a mass ratio of 1:0.8, stirred at a speed of 300 r / min for 30 minutes, and then allowed to stand for 35 minutes, washed with deionized water, dried at 105°C for 9 hours, and then ground by a ball mill at a speed of 400 r / min for 2 hours and passed through a 200-mesh sieve to obtain the modified bentonite.
[0032] Preparation of adhesive: Step 1: Place 100 parts of silicone resin and 25 parts of epoxy resin in a reaction kettle by weight, and stir at 155° C. and 270 r / min for 5 hours to obtain a mixture A; Step 2: Add 7 parts of modified bentonite to mixture A, stir at 270 r / min at 75° C. for 30 min, then add 5 parts of nano-silicon dioxide and continue stirring for 30 min to obtain mixture B; Step 3: Continue to add 35 parts of diethylenetriamine, 3 parts of 2-ethyl-4-methylimidazole, 7 parts of ethylene glycol diglycidyl ether and 3 parts of KH550, and stir at room temperature at a speed of 270 r / min for 10 minutes to obtain the adhesive.
[0033] Preparation of ultra-clean containers with hydrofluoric acid-resistant lining membranes: S1. Melting fusible polytetrafluoroethylene at 335°C, extruding, maintaining the temperature and expanding the fusible polytetrafluoroethylene to a size that is consistent with the mold through a blowing process, to obtain an inner lining film having a thickness of 0.3 mm, wherein the extrusion speed is 22 m / min, the extrusion pressure is 12 MPa, and the blowing pressure is 0.7 MPa; S2, treating the inner lining film by a corona process, wherein the parameters of the corona treatment process are: voltage of 13 kV, discharge frequency of 23 KHz, and treatment time of 8 s, to prepare a pretreated inner lining film; S3. Coat the inner wall of the ultra-clean barrel base with a silane coupling agent KH560 solution with a mass fraction of 15%. After sufficient drying, evenly apply the adhesive on the pretreated lining film surface, and then bond it to the inner wall of the ultra-clean container with the adhesive. Maintain the pressure by blowing at a blowing pressure of 0.7 MPa. After curing at 45°C for 8 hours, perform a press-coating treatment for 2 hours. After washing with deionized water and drying at room temperature, obtain the ultra-clean container with a hydrofluoric acid-resistant lining film, wherein the pressing temperature is 40°C and the pressure is 0.2 MPa.
[0034] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that the bentonite in Comparative Example 1 is not subjected to property modification treatment, and the other operations are the same.
[0035] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in Comparative Example 2, no nano-silicon dioxide is added during the preparation of the adhesive, and the other operations are the same.
[0036] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that in Comparative Example 3, no modified bentonite is added during the preparation of the adhesive, and the other operations are the same.
[0037] Performance Test: 1. Test method for anti-penetration performance of adhesive: A glass magnesium board with uniform material is divided into several areas of equal area, and the adhesive of each embodiment and comparative example is evenly coated on the corresponding area with a coating thickness of 2 mm. After curing for 6 hours, a hydrofluoric acid solution with a mass fraction of 10% is dripped on the adhesive. After 20 minutes, the remaining amount of solution on the glass magnesium board is calculated. At the same time, the glass magnesium board without adhesive coating is used as a blank control. The results are shown in Table 1: Table 1
[0038] 2. Adhesion test: Refer to GB / T 9286-1998 standard to test the adhesion between the lining film and the inner wall surface of the container in the examples and comparative examples. The measured adhesion is divided into 6 levels from 0 to 5, with 0 being the best adhesion and 5 being the worst adhesion. 3. Acid resistance test: Hydrofluoric acid resistance: The container prepared in the embodiment and the comparative example is filled with a 15% volume fraction hydrofluoric acid aqueous solution, and after 12 hours, the adhesion is measured according to the method described in the adhesion test, which is the hydrofluoric acid resistance; Resistance to 98% concentrated sulfuric acid: The containers prepared in the examples and comparative examples were filled with 98% concentrated sulfuric acid by mass. After 12 hours, the adhesion was measured according to the method described in the adhesion test, i.e., the ability to resist 98% concentrated sulfuric acid. The test results are shown in Table 2 below: Table 2
[0039] According to the above data, the ultra-clean container containing the lining film prepared by the present invention has excellent resistance to hydrofluoric acid and 98% concentrated sulfuric acid, and the lining film has good adhesion to the inner wall of the barrel.
[0040] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A process for preparing an ultra-clean container with a hydrofluoric acid-resistant lining film, characterized in that: The ultra-clean container substrate and the inner lining film are bonded by an adhesive, wherein the material of the container substrate is high-density polyethylene, and the material of the inner lining film is fusible polytetrafluoroethylene, and the preparation process includes the following: S1. Melt the fusible polytetrafluoroethylene at 320-335°C, and then extrude it. Keep the temperature and use clean air blowing process to expand the fusible polytetrafluoroethylene to match the mold to obtain an inner lining film. The thickness of the inner lining film is 0.3 mm. The extrusion speed is 18-22 m / min, the extrusion pressure is 8-12 MPa, and the blowing pressure is 0.5-0.7 MPa. S2, treating the inner lining film by a corona process, wherein the parameters of the corona treatment process are: voltage of 10-13 kV, discharge frequency of 20-23 KHz, to prepare a pretreated inner lining film; S3. Coat the inner wall of the ultra-clean container substrate with a silane coupling agent KH560 solution with a mass fraction of 15%. After sufficient drying, evenly apply the adhesive on the pretreated surface of the lining film, and then bond it to the inner wall of the ultra-clean container with the adhesive. Maintain the pressure by blowing, and the blowing pressure is 0.5~0.7MPa. After curing, it is subjected to a press coating treatment for 1~2h. After washing with deionized water and drying at room temperature, the ultra-clean container with a hydrofluoric acid-resistant lining film is obtained, wherein the pressing temperature is 20~40°C and the pressure is 0.1~0.2MPa.
2. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 1, characterized in that: In step S3, the curing temperature is 35-45° C. and the curing time is 5-8 hours.
3. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 1, characterized in that: In step S3, the preparation process of the adhesive is as follows: Step 1: Place 80-100 parts of silicone resin and 20-25 parts of epoxy resin in a reaction kettle, heat and stir at 130-155° C. for 3-5 hours to obtain a mixture A; Step 2: Add 4-7 parts of modified bentonite to mixture A, stir at 60-75° C. for 30 min, and continue to add 3-5 parts of nano-silicon dioxide and continue to stir for 30 min to obtain mixture B; Step 3: Continue to add 25-35 parts of curing agent, 1-3 parts of accelerator, 5-7 parts of diluent and 1-3 parts of silane coupling agent, and stir at room temperature for 8-10 minutes to obtain the adhesive.
4. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 3, characterized in that: In step 1, the organic silicone resin is methyl silicone resin.
5. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 3, characterized in that: In step 2, the preparation process of the modified bentonite is as follows: At room temperature, aluminum chloride and deionized water are mixed in a mass ratio of 1:5, stirred at a speed of 200 r / min for 2-3 hours, bentonite is added and stirred for 1-3 hours, and the pretreated bentonite is obtained after filtration; bentonite and polyoxyethylene hydrogenated castor oil are mixed in a mass ratio of 1: (0.5-0.8), stirred at a speed of 300 r / min for 30 minutes, and then allowed to stand for 25-35 minutes, washed with deionized water, dried at 95-105° C. for 7-9 hours, and then ground by a ball mill at a speed of 400 r / min for 2 hours and passed through a 200-mesh sieve to obtain the modified bentonite.
6. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 3, characterized in that: In step 3, the diluent is ethylene glycol diglycidyl ether.
7. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 3, characterized in that: In step three, the curing agent is one of ethylenediamine, diethylenetriamine and polyamide curing agent.
8. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 3, characterized in that: In step three, the accelerator is one of accelerator DMP-30 and 2-ethyl-4-methylimidazole.
9. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 3, characterized in that: In step three, the silane coupling agent is one of KH550, KH560 and KH570.
10. The process for preparing the ultra-clean container with a hydrofluoric acid resistant lining film according to claim 3, characterized in that: During the preparation of the adhesive, the stirring speed is 200-270 r / min.